Persepsi Karyawan terhadap Peran Internal Audit Sebagai Divisi Baru Dalam Upaya Mewujudkan Good University Governance (Studi Kasus PTS XYZ di Semarang) - Herawati, Lisa Dwi; Hastuti, Theresia Dwi (APSSAI ACCOUNTING REVIEW, 2022)
This study aims to determine employee perceptions of the role of internal audit at PTS XZY in Semarang as a new division and can be used as evaluation material in increasing the role of internal audit in a university. This study uses a qualitative research method with a case study approach at PTS XYZ. The data collection methods of this research are interviews, observation and documentation. The result of this research is that employees' perception of Internal Audit at PTS XYZ as a new division has a positive impact on financial governance in the Unit, Bureau, or faculty, although there are still activities that have not been implemented. This is supported by the statement of 75% of respondents who think that the role of internal audit at PTS XYZ is as consulting because it is able to provide recommendations to auditees on audit findings, although there are 25% of respondents who think that internal audit is currently unable to provide solutions and only tends to blame.